‘They have deliberately left us to kill each other’: dehumanisation and gang violence in African* townships - G. Nokukhanya Ndhlovu (Cogent Social Sciences, 2024)
This article discusses the dehumanisation experienced by marginalised South African ekasi (African township) youths. More particularly, it explores how dehumanisation in the two African townships of Bophelong and Nyanga in South Africa has increased young people’s vulnerability to youth gangs. The research question is: how does dehumanisation contribute to gang violence in African townships? The paper adopts a qualitative approach and purposive sampling. The findings show that there is a strong link between dehumanisation and youth vulnerability to gangs. Many young people are excluded from access to fundamental human rights, which exposes them to multidimensional development challenges and pushes them towards a life of gangs and crime. Government, civil society, and the private sector must work together to intentionally address the root causes of youth gang violence in African townships.